Ingested air rifle pellet associated with acute perforated appendicitis (Revista Argentina de Cirugía, 2021)
We report the case of a 28-year-old male patient with a history of voluntary ingestion of a metallic pellet 20 days before who was transferred to our department with typical symptoms of acute appendicitis. Under that circumstances he underwent conventional appendectomy. The analysis of the preoperative imaging tests and the intraoperative findings help to identify the association between the foreign body and acute appendicitis. Ingestion of foreign bodies, either accidental or voluntary, is an extremely uncommon cause of acute appendicitis; thus, there are few reports in the international literature. This is the first case reported in Argentina..
Keywords: appendicitis; ingested foreign body; air gun bullet